The Impact of the COVID-19 Pandemic on Head and Neck Surgery Training: A Brazilian National Survey - Leite, Ana Kober; Matos, Leandro Luongo; Cernea, Claudio R.; Kowalski, Luiz Paulo (International Archives of Otorhinolaryngology, 2021)
Introduction The COVID-19 pandemic has had a high impact on surgical training around the world due to required measures regarding the suspension of elective procedures and the dismissal of nonessential personnel.Objectives To understand the impact the pandemic had on head and neck surgery training in Brazil.Methods We conducted a 29-question online survey with head and neck surgery residents in Brazil, assessing the impact the pandemic had on their training.Results Forty-six residents responded to the survey, and 91.3% of them reported that their residency was affected by the pandemic, but most residents were not assigned to work directly with patients infected with the new coronavirus (71.4%). All residents reported decrease in clinic visits and in surgical procedures, mostly an important reduction of ∼ 75%. A total of 56.5% of the residents described that the pandemic has had a negative impact on their mental, health and only 4 (8.7%) do not have any symptoms of burnout. The majority (78.3%) of the residents reported that educational activities were successfully adapted to online platforms, and 37% were personally infected with the virus.Conclusion Most surgical residencies were greatly affected by the pandemic, and residents had an important decrease in surgical training. Educational activities were successfully adapted to online modalities, but the residency programs should search for ways of trying to compensate for the loss of practical activities.
Keywords: Internship And Residency; surgery; COVID-19; head and neck